ERRATA - Masabumi Masuko (Japanese Society of Tribologists, 2016)
Volume and issue: Vol.11, No.1 (2016)Page: pp.13-23Title: Improvement in Mixed Lubrication Characteristics of Electromagnetic Clutch Coated with DLC-Si Film by Controlling Surface Roughness and Providing Micro-grooveAuthor(s): Junji Ando, Takeshi Yamaguchi and Kazuo Hokkirigawa